ALTERASI, MINERALISASI, DAN ASOSIASI MINERAL SULFIDA PEMBAWA EMAS ENDAPAN EPITERMAL SULFIDASI TINGGI DAERAH RAMBA JORING, KECAMATAN BATANGTORU, KABUPATEN TAPANULI SELATAN, SUMATRA UTARA - SHOLIHAH , FATIYAH
The research area is located in Ramba Joring, Batangtoru Subdistrict, South Tapanuli Regency, North Sumatra Province with an area sized ±0.23 km2. Ramba Joring is one of the contract of work area of PT Agincourt Resources that is currently explored. The purposes of this research are to determine geological condition, design an alteration-mineralization zone, also to determine the correlation between sulfide minerals and Au grade. To achieve those goals, some methods such as detailed bore core logging from 7 different wells, petrographic analysis of 15 samples, mineragraphic analysis of 22 samples, clay and oxide minerals analysis using ASD and assay Au, Ag, Cu, As, SCIS geochemistry analysis were used. Lithostratigraphic units of Ramba Joring that formed on Late Miocene–Pliocene consist of 2 units, they are Volcanic Andesite Hornblenda Unit and Phreatic Breccia Unit. All of those units had undergone alteration-mineralization process on Pliocene. There are four alteration zones, they are Massive-Vuggy Silica Zone, Alunite-Dickite-Quartz Zone, Smectite-Illite-Quartz Zone and Steam Heated Zone. Pyrite occure in all alteration zones, enargite-covellite-hematite occure in both of Alunite-Dickite-Quartz Zone and Massive-Vuggy Silica Zone. Mineralization paragenesis can be subdivided into two phases, there are high sulphidation epithermal and supergene oxidation. Based on mineragraphic analysis, it can be seen that Au > 5 ppm indicated by presence of pyrite, while Au < 5 ppm indicated association of pyrite, enargite and covellite. Oxide zone is determined by overlaying SCIS zone and zone of the presence of hematite. Based on overlaying oxide zone and metal zone it is known that Au-Ag can exist in both of oxide zone and sulfide zone, while Cu-As exist in sulfide zone.